El Diario: Una forma de difundir resultados de investigaciones científica - Balarezo López, Gunther (2015)
It was a literature review of various newspapers between June and October of 2012 published in the city of Lima, taking only the news related to health sciences. The journal can be a primary source of dissemination of research results, and later, the health care professional to find out more about the study in which you are interested. The publication of such news should be supervised by a health care professional to prevent the dissemination of information that may be confusing. Also, these results may encourage professionals and students from health to develop projects to study these results in our country.